Soil microbial mechanisms promoting ultrahigh rice yield. (April 2020) - Zhong, Yangquanwei; Hu, Jihong; Xia, Qiongmei; Zhang, Shilai; Li, Xin; Pan, Xiangyu; Zhao, Ruoping; Wang, Ruiwu; Yan, Weiming; Shangguan, Zhouping; Hu, Fengyi; Yang, Congdang; et al.
Abstract: Improving rice yield potential is crucial for global food security. Taoyuan, China, is famous worldwide as a special ecosite for ultrahigh rice yield. Climatological factors affecting this phenomenon have been identified, but the potential molecular processes and environmental mechanisms promoting ultrahigh yield remain mysteries. This study identifies soil biotic factors affecting ultrahigh yield, considering soil microbial community structure and metagenomic functions during four key rice growth stages, together with results from nitrogen enrichment experiments and rice root transcriptome analysis. Our results show that Taoyuan has more diverse bacterial taxa, less diverse fungal taxa, and a 10-fold-stronger connection among microbial taxa as well as a significantly higher proportion of nutrient transport functions than a regular site. Notably, our metagenomic analysis shows that Taoyuan contains more taxa with nitrogen metabolism functions and a higher abundance of genes involved in the nitrification process (e.g., hydroxylamine oxidoreductase and nitric oxide dioxygenase), promoting effective transformation of ammonium (NH4 + ) to nitrate (NO3 − ) in rice fields and stimulating high expression of nitrate transporters in rice roots, leading to ultrahigh yields. Our results indicate that soil microbiota contribute to ultrahigh rice yield in Taoyuan, and indicate that nitrogen metabolism functions could be one of the mechanism for the ultrahigh yield of rice. Highlights: Soil microbial metagenomic characteristics were investigated in an ultrahigh rice field (Taoyuan). Taoyuan has more diverse bacterial and less diverse fungal taxa than a regular site. Taoyuan has a 10-fold stronger connection among microbial taxa than a regular site. Taoyuan contains more genes involved in the nitrification process, promoting ultrahigh rice yield.